2013
DOI: 10.1007/s11606-012-2308-x
|View full text |Cite
|
Sign up to set email alerts
|

Key Barriers to Medication Adherence in Survivors of Strokes and Transient Ischemic Attacks

Abstract: BACKGROUND: Even though medications can greatly reduce the risk of recurrent stroke, medication adherence is suboptimal in stroke survivors. OBJECTIVE: To identify key barriers to medication adherence in a predominantly low-income, minority group of stroke and transient ischemic attack (TIA) survivors. DESIGN: Cross-sectional study. PARTICIPANTS: Six hundred stroke or TIA survivors, age ≥ 40 years old, recruited from underserved communities in New York City. MAIN MEASURES: Medication adherence was measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 42 publications
2
61
0
9
Order By: Relevance
“…In previous studies, limited access to medication [3,23,24,28] and inadequate healthcare system where reported as barriers for medication adherence affecting the relationship between patients and healthcare professionals. Since the French healthcare system allows free access to medication, it could explain why these issues were not reported here and probably do not constitute a major barrier for treatment compliance in French stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, limited access to medication [3,23,24,28] and inadequate healthcare system where reported as barriers for medication adherence affecting the relationship between patients and healthcare professionals. Since the French healthcare system allows free access to medication, it could explain why these issues were not reported here and probably do not constitute a major barrier for treatment compliance in French stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the specific issue of medication adherence, Leventhal's self-regulatory model of illness behavior was highly relevant [3,22]. In previous studies, this model supported the relationship between medication adherence and beliefs and expectations regarding treatments [8,12,18,23,24]. In addition to collecting information from patients and caregivers, it seemed relevant to collect experiences from healthcare professionals as they play a significant role in the patients' care management [25].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, 70% of stroke survivors have hypertension [9], 77% have impaired glucose tolerance or type 2 diabetes mellitus [10], and 18 to 44% are obese [11]. In addition, individuals with stroke are not physically active, 40% report nonadherence to medication regimens [12], and many have unhealthy dietary patterns [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that poor adherence was associated with cognitive dysfunction, a high number of treatments, higher medication copayment and a prolonged time between symptoms and neurological evaluation at acute phase. Some behavioral factors are also to consider, such as concerns about medication (fear of side effects or dependency), complexity of the treatment, lack of perceived benefit for these treatments and perceived discrimination from the healthcare system [24, 31, 32]. …”
Section: Discussionmentioning
confidence: 99%